Right ureteric reconstruction with vascularised interpositional appendix graft in retroperitoneal leiomysarcoma - Sohail, Mushtaq; Loke, Sheih Nee; Sim, Sze Kiat; Nik Azim, Nik Abdullah (Malaysian Medical Association, 2021)
We present here a case of a 66-year-old lady who was diagnosed with right iliac fossa retroperitoneal leiomyosarcoma at Hospital Umum Sarawak. The challenge in this case was the extension of tumour with the involvement of her right ureter causing proximal hydroureter and hydronephrosis. After resection of tumour en-block with the involved segment of ureter, it was not possible to repair the ureteric defect directly. We used interpositional vascularized appendix graft to repair this large (7 cm) ureteric defect. We describe here this uncommon technique of ureter reconstruction.